Immature CD4+CD8+ thymocytes are preferentially infected by measles virus in human thymic organ cultures. - Yukari Okamoto (Public Library of Science (PLoS), 2012)
Cells of the human immune system are important target cells for measles virus (MeV) infection and infection of these cells may contribute to the immunologic abnormalities and immune suppression that characterize measles. The thymus is the site for production of naïve T lymphocytes and is infected during measles. To determine which populations of thymocytes are susceptible to MeV infection and whether strains of MeV differ in their ability to infect thymocytes, we used ex vivo human thymus organ cultures to assess the relative susceptibility of different subpopulations of thymocytes to infection with wild type and vaccine strains of MeV. Thymocytes were susceptible to MeV infection with the most replication in immature CD4(+)CD8(+) double positive cells. Susceptibility correlated with the level of expression of the MeV receptor CD150. Wild type strains of MeV infected thymocytes more efficiently than the Edmonston vaccine strain. Thymus cultures from children ≥3 years of age were less susceptible to MeV infection than cultures from children 5 to 15 months of age. Resistance in one 7 year-old child was associated with production of interferon-gamma suggesting that vaccination may result in MeV-specific memory T cells in the thymus. We conclude that immature thymocytes are susceptible to MeV infection and thymocyte infection may contribute to the immunologic abnormalities associated with measles.